The environment and externality : theory, algorithms and applications - Yang, Zili, 1957- (Cambridge : Cambridge University Press, 2021)
This innovative book models pollution mitigation as a negative externality whilst also providing desirable and useful solutions, such as establishing the triangular equivalence relationship among the Lindahl equilibrium without transfers, the Nash bargaining solution with the payoffs of the Cournot-Nash equilibrium as the status quo point, and the social optimum under the Lindahl weights. By introducing programming algorithms to validate these relationships numerically, Zili Yang bridges the gap between analytical results and empirical modelling, ultimately solving the Lindahl equilibrium and hybrid Nash equilibria in the influential RICE model. This text demonstrates the complexity and variety of environment externality problems, ranging from mixed externality to correlated externalities to environmental externality under IRS and policy applications. Integrating theory, algorithms and applications in a comprehensive framework, The Environment and Externality will benefit scholars and students working across environmental, resource and climate change economics.
Title from publisher's bibliographic system (viewed on 01 Jan 2021).
Keywords: Environmental economics -- Mathematical models; Externalities (Economics); Equilibrium (Economics)